Membangun Kebiasaan Sehat Melalui Praktik Sikat Gigi dan Cuci Tangan Enam Langkah di TK Pembangunan V YAPIS Distrik Heram, Kota Jayapura, Papua - Elieser Elieser; Trajanus Jembise; Ferdinant M. Djawa; Dais Iswanto (LPPM Uncen, 2026)
Clean and healthy living habits from an early age are needed as provisions for achieving prosperity in the future. However, this is a challenge because most children are not yet able to carry them out properly and consistently. This community service aims to train and improve the skills of performing six-step handwashing and proper toothbrushing practices in children at YAPIS Heram Kindergarten in Jayapura City. The community service method was carried out using an initial observation and coordination approach, brief and clear education, repeated demonstrations, direct practice, and final evaluation. The activity involved two community service teams and five accompanying teachers from the school and a general assistant, as well as 24 kindergarten children as participants. Data analysis was conducted descriptively by comparing conditions before and after the intervention on two main indicators. The results of the activity showed an increase in the ability to practice toothbrushing from 7 children (29.2%) to 16 children (66.7%), while the practice of six-step handwashing increased from 3 children (12.5%) to 14 children (58.3%). At the same time, the category of not being able to in both indicators decreased sharply to only 2 children (8.3%). The activity's conclusions showed changes in competency in practicing six-step handwashing and proper toothbrushing. Furthermore, demonstrations and hands-on practice effectively helped children better understand and practice healthy behaviors. Teacher involvement and a pleasant learning environment were crucial factors in supporting the activity's success. This activity not only provided practical benefits for the school and children but also reinforced a simple, measurable, and easily applicable practice-based community service model for early childhood health education.